CTNNBIP1 modulates keratinocyte proliferation through promoting the transcription of β‐catenin/TCF complex downstream genes. (22nd July 2020) - Wang, C.; Wang, H.; Peng, Y.; Zeng, B.; Zhang, Y.; Tang, X.; Mi, L.; Pan, Y.; Yang, Z.
Abstract: Background: During psoriasis initiation and development, deregulations in signalling pathways and gene expression are observed. Methods: Herein, we downloaded seven sets of microarray mRNA expression profiles showing differentially expressed genes in psoriasis lesion skin and non‐lesion skin tissues and three sets of RNA‐seq data and analysed these online data attempting to screen for crucial genes related to keratinocyte proliferation and psoriasis development. The expression of CTNNBIP1 in psoriasis patients and IMQ mouse model skin tissues were examined by RT‐PCR, immunoblotting and IHC. The functions of CTNNBIP1 on HaCaT cell proliferation, apoptosis and β‐catenin/TCF complex were measured by MTT, EdU, flow cytometry, IF, luciferase assays and immunoblotting. Results: The expression of catenin beta interacting protein 1 (CTNNBIP1) was remarkably downregulated within psoriasis lesion skin tissue samples compared to that within non‐lesion skin tissues based on both online data and experimental results. In response to a period of different therapies, respectively, CTNNBIP1 expression could be rescued in lesion skin tissues. Within IMQ‐induced psoriasis‐like dermatitis in mice, CTNNBIP1 silence further aggravated psoriatic phenotypes. In human immortalized keratinocytes, HaCaT cells, CTNNBIP1 silence significantly inhibited cell apoptosis and promoted cell proliferation. Regarding the molecular mechanism, CTNNBIP1 silence in HaCaT cells promoted β‐catenin nucleus translocation, enhanced the transcriptional activity of TCF4 and increased β‐catenin/TCF complex downstream c‐Myc and cyclin D1 proteins, and also increased the expression of cell proliferation marker ki‐67. In contrast to CTNNBIP1, the expression of c‐Myc and cyclin D1 showed to be dramatically upregulated within psoriasis lesion tissue samples than that within non‐lesion tissue samples. Within tissues, c‐Myc and cyclin D1 showed to be negatively correlated with CTNNBIP1, respectively. Conclusions: We identify CTNNBIP1 as an abnormally downregulated gene in psoriasis. CTNNBIP1 silence significantly disturbs the proliferation of keratinocytes through promoting the transcription of β‐catenin/TCF complex downstream genes.